A molecular assessment of species diversity in Tympanopleura and Ageneiosus catfishes (Auchenipteridae: Siluriformes) - Shizuka Hashimoto; Lúcia H. Rapp Py‐Daniel; Jacqueline S. Batista (Journal of Fish Biology, 2020)
In order to test the congruence of genetic data to the morphologically defined Neotropical catfish genera Tympanopleura and Ageneiosus and explore species diversity, we generated 17 DNA barcodes from five of six species of Tympanopleura and 12 of 13 species of Ageneiosus . To discriminate limits between species, an automatic barcode gap discovery (ABGD), a generalised mixed yule‐coalescent model (GYMC) and fixed distance thresholds Kimura two‐parameter (K2P; 3%) were used to discriminate putative species limits from the DNA barcodes. The ABGD, GMYC and K2P methods agreed by each generating 13 clusters: six in Tympanopleura (five nominal plus one undescribed species) and seven in Ageneiosus . These clusters corresponded broadly to the described species, except in the case of the Ageneiosus ucayalensis group ( A. akamai , A. dentatus , A. intrusus , A. ucayalensis , A. uranophthalmus and A. vittatus ). Haplotype sharing and low divergences may have prevented molecular methods from distinguishing these species. We hypothesise that this is the result of a recent radiation of a sympatric species group distributed throughout the Amazon Basin. One putative new species of Tympanopleura was also supported by the molecular data. These results taken together highlight the utility of molecular methods such as DNA barcoding in understanding patterns of diversification across large geographic areas and in recognising overlooked diversity.